Assessing dynamic treatment strategies - Berzuini, Carlo; Dawid, Philip; Didelez, Vanessa (Causality, 2012)
This chapter contains sections titled: Introduction Motivating example Descriptive versus causal inference Notation and problem definition HIV example continued Latent variables Conditions for sequential plan identifiability Graphical representations of dynamic plans Abdominal aortic aneurysm surveillance Statistical inference and computation Transparent actions Refinements Discussion Acknowledgements References